2017
DOI: 10.1186/s13104-017-2555-3
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent deliveries in semi-urban Cameroon: prevalence and adverse neonatal outcomes

Abstract: ObjectivesAdolescent pregnancies are high risk due to the increased probability of adverse outcomes; as adolescents are usually considered to be ill-equipped to deal with the burden of pregnancy. We sought to determine the prevalence of adolescent deliveries in a secondary-level care hospital in semi-urban Cameroon-Bamenda, the adverse neonatal outcomes and to assess if previous obstetric history could preclude adolescents from having adverse outcomes in their present pregnancy.ResultsThe prevalence of adolesc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
4
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 9 publications
2
21
4
3
Order By: Relevance
“…The prevalence of adolescent deliveries (8.2%) found among the study population fell within the 6–14% range reported in other studies in Sub-Saharan African countries [ 3 , 16 ]. It is however slightly lower than that the prevalence recently observed in Buea (9.9%) and Bamenda (8.7%), both sub-urban settings in the country [ 13 , 18 ]. It was also much lower than the prevalence of 20.4% obtained in a rural area in Cameroon [ 19 ].…”
Section: Main Textcontrasting
confidence: 63%
See 1 more Smart Citation
“…The prevalence of adolescent deliveries (8.2%) found among the study population fell within the 6–14% range reported in other studies in Sub-Saharan African countries [ 3 , 16 ]. It is however slightly lower than that the prevalence recently observed in Buea (9.9%) and Bamenda (8.7%), both sub-urban settings in the country [ 13 , 18 ]. It was also much lower than the prevalence of 20.4% obtained in a rural area in Cameroon [ 19 ].…”
Section: Main Textcontrasting
confidence: 63%
“…Many authors have reported an increase in the following adverse maternal and perinatal outcomes in adolescent pregnancies: preeclampsia/eclampsia, operative deliveries, maternal death, low birth weight, preterm deliveries, still births and neonatal asphyxia [ 12 14 , 18 , 19 ]. Our study showed that pregnant adolescents had higher rates of LBW infants, preterm delivery and neonates with low 5-min APGAR.…”
Section: Main Textmentioning
confidence: 99%
“…In addition to psychiatric difficulties, many physical illnesses are more frequent in adolescent pregnancies. 24,25 However, in our study, there was no difference between the groups in terms of physical problems. The rates of having no physical and mental disorders in our study were higher in the adolescent pregnancies.…”
Section: Discussioncontrasting
confidence: 72%
“…Throughout literature, only one study which tried to assess pregnancy outcomes between these two groups of adolescents was found. This was a study carried out in a semi-urban region—Bamenda in Cameroon and showed that adolescent primipas were just as likely to have LBW, HBW, asphyxia and caesarean sections as adolescent multipas [ 10 ]. The sample size used in this study was however small to get significant differences between the two groups.…”
Section: Main Textmentioning
confidence: 99%